Peran Agency Cost terhadap Kebijakan Dividen pada Pasar yang Sedang Berkembang (Studi pada Bursa Efek Indonesia) - Sudarma, Made (Jurnal Aplikasi Manajemen, 2011)
This research was aimed at finding the influence of agency cost on dividend policy in emerging market. Sample of this research was manufacturing companies listed in Indonesia Stock Exchange for 2005-2007, taken using purposive sampling method. The result of the partials test shows that collateralizable asset has influence on dividend payout ratio with negatif direction. Variables of insider ownership, disper sion of ownership, institutional ownership, and free cash flow do not have any influences on dividend payout ratio. It is caused because there is no real separation between ownership function and control function of the public companies in Indonesia. The result of simultaneous test shows that the agency cost has no influence on dividend policy, represented by dividend payout ratio.